Gateways to New Learnings: Walking to Re/Vision an International Practicum - Cho, Christine L.; Corkett, Julie K (Journal of the Canadian Association for Curriculum Studies, 2021)
We engage in a creative exploration of the ways in which a walk provided us with insights into how we might enhance the curriculum for a teacher education international practicum in Italy. Drawing from a currere framework, we shifted to mindful walking, and we tell our story in three parts that represent the various stages of our mindful engagement: intention; attention; and attitude. Walking in this way provided the impetus for us to re-examine the curriculum of the international practicum. We argue that mindful walking has the potential to increase observation skills and open up ways to develop deeper cultural connections in an international practicum. We consider what those connections could do to enhance the practicum and our teacher candidates’ experience.